2019
DOI: 10.1002/fsn3.1358
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of saponin composition and comparison of the antioxidant activity of various parts of the quinoa plant (Chenopodium quinoa Willd.)

Abstract: Quinoa plant is a valuable food crop because of its high nutritional and functional values. Total saponin content, sapogenins, polyphenol, and flavonoid contents and antioxidant activities were analyzed in various parts of quinoa plants, including sprout, seeds, bran, pericarp, leave, stem, and root. Quinoa seeds (QS) had significantly higher sapogenin content than quinoa stem (QT), quinoa leaves (QL), and quinoa roots (QR). Quinoa saponin was mainly composed of phytolaccagenic acid. Quinoa root (QR) had the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(70 citation statements)
references
References 29 publications
5
59
0
Order By: Relevance
“…The effect of soaking, dehulling and germinating was also investigated, and a lower TPC was found in soaked and dehulled seeds, while an almost three-fold increase in TPC occurred in germinated seeds. The lowest TPC value (14.37 mg GAE 100 g −1 dm) among quinoa seeds from Asia was found in quinoa samples grown in Korea (Table 2) [20].…”
Section: Quantitation Of Phenolic Compounds By Spectrophotometric Assaysmentioning
confidence: 92%
See 1 more Smart Citation
“…The effect of soaking, dehulling and germinating was also investigated, and a lower TPC was found in soaked and dehulled seeds, while an almost three-fold increase in TPC occurred in germinated seeds. The lowest TPC value (14.37 mg GAE 100 g −1 dm) among quinoa seeds from Asia was found in quinoa samples grown in Korea (Table 2) [20].…”
Section: Quantitation Of Phenolic Compounds By Spectrophotometric Assaysmentioning
confidence: 92%
“…As for quinoa grown in Asian countries, it was not possible to define a range for flavonoid content, as different flavonoids were used as standards for the calibration. Lim et al reported 45.88 mg Rutin Equivalent (RE) 100 g −1 dm for TFC in seeds from Korean crops (Table 2) [20]. Both free and bound flavonoids were reported for samples from China (Table 2) [16,18], but these values are not comparable since rutin and quercetin were used as standards for the calibration.…”
Section: Quantitation Of Phenolic Compounds By Spectrophotometric Assaysmentioning
confidence: 99%
“…Quinoa contains abundant bioactive substances including saponins, polyphenols and avonoids (Alvarez-Jubete et al 2010). These secondary metabolites accumulate richly in roots (Lim et al 2020). In our research, transgenic hairy roots produced betacyanins due to the expression of the genes from pX11, which will be ideal approach for commercially production of nutritious betacyanins from quinoa hairy roots.…”
Section: Discussionmentioning
confidence: 94%
“…The content of total phenolic compounds in extracts was determined by the coloration method (Lim et al., 2020; Xie et al., 2019). 1.0 ml of DRE was mixed with 1 ml of foline‐phenol solvent.…”
Section: Methodsmentioning
confidence: 99%
“…The content of total phenolic compounds in extracts was determined by the coloration method (Lim et al, 2020;Xie et al, 2019).…”
Section: Quantitative Analyses Of Biologically Active Compounds In Drementioning
confidence: 99%